Training Contracts, Employee Turnover, and the Returns from Firm-Sponsored General Training - Mitchell Hoffman; Stephen V. Burks (Institute of Labor Economics (IZA), 2017)
Firms may be reluctant to provide general training if workers can quit and use their gained skills elsewhere. "Training contracts" that impose a penalty for premature quitting can help alleviate this inefficiency. Using plausibly exogenous contractual variation from a leading trucking firm, we show that two training contracts significantly reduced post-training quitting, particularly when workers are approaching the end of their contracts. Simulating a structural model, we show that observed worker quit behavior exhibits aspects of optimization (for one of the two contracts), and that the contracts increased firm profits from training and reduced worker welfare relative to no contract.
Keywords: J24; M53; J41; 330; training contract; firm-sponsored general training; organizations; trucking; truck driver; truckload